Phonological Differences Between Standard Javanese and Banyumas Dialect of Javanese - Ricky Giovani Reynaldi (Compendium: Journal of Cultural, Literacy, and Linguistic Studies, 2017)
Dialect is a language form which is unique to specific region or society. Javanese language has many dialects, such as Mataraman dialect or known as standard Javanese, and Banyumas dialect. This study investigates phonological differences between these two dialects of Javanese language using Phonological Rules and Distinctive Features. There are sound changes between 2 dialects, such as dino in standard Javanese and dina in Banyumas dialect, moto and mata,wae and bae, and so on. There is also deletion process which occurs in final position, such as koe in standard Javanese and ko in Banyumas dialect. This study investigates all phonological features and differences between standard Javanese and Banyumas dialect.